Teknologi Dalam Pendidikan: Membangun Wacana Pendidikan Indonesia Masa Depan - Rhyno Fairuz Melin (Pusat Riset dan Inovasi Nasional, 2024)
Technology plays a crucial role in various fields, especially in the realm of education. With the rapid advancement of technology, proficient education is necessary to prepare for a promising future. Research focuses on aspects that can facilitate the development of discourse on Indonesian education in the future, integrated with technology. This study employs a qualitative descriptive method with literature review, examining various sources related to the discussed topic. The findings elucidate strategies for constructing a discourse in the future of education integrated with technology. Moreover, the results indicate that effective educational discourse entails ideas that do not neglect the objectives and functions of education itself.